Can 18F-FDG PET/CT diagnose malignant change in benign chondroid tumors?. Issue 6 (June 2019) - Purandare, Nilendu C.; Puranik, Ameya; Shah, Sneha; Agrawal, Archi; Puri, Ajay; Gulia, Ashish; Nayak, Prakash; Rekhi, Bharat; Rangarajan, Venkatesh
Abstract : Aim: The aim of this study was to determine whether fluorine-18 fluorodeoxyglucose ( 18 F-FDG) PET/computed tomography (CT) can diagnose malignant change in benign chondroid tumors. Patients and methods: This study included patients with clinicoradiological features of a chondroid tumor who were referred for a 18 F-FDG PET/CT study to evaluate clinical suspicion of malignant change. Metabolic characteristics of the suspected lesion in the form of maximum standardized uptake value (SUVmax ) was obtained and compared with histopathology. In patients who were treated conservatively and for whom histopathology was not available, stability of the lesion on clinical/radiological follow-up was used as reference standard. Receiver operating characteristic curve analysis was performed to obtain a SUVmax cutoff value to differentiate between benign and malignant lesions. Results: Clinical and imaging data of 66 patients was available for analysis. Malignancy was confirmed by histopathology in 40/66 (60.6%) patients with grade 2 chondrosarcomatous change seen in majority. In 26 patients, the final diagnosis was benign tumor (osteochondroma, n =19; enchondroma, n =7). Median SUVmax of malignant lesions was significantly higher compared with the benign lesions (4.0 vs. 2.1, P =0.00). A SUVmax cutoff of 3.1 could differentiate a benign lesion from those with malignant transformation with a sensitivity of 90.3% and specificity of 87% (area under the curve=0.92). Dedifferentiated sarcomas showed a significantly higher uptake than rest of the sarcoma types. Conclusion: 18 F-FDG PET/CT can detect malignant change in benign chondroid neoplasms by showing higher metabolic activity in the area of sarcomatous transformation. It can also identify focus of dedifferentiation which has prognostic and therapeutic implications.